Innovation in the design of inclusive toys: Development and evaluation of a prototype for visually impaired children - dos Santos, Aline Darc Piculo [UNESP]; Medola, Fausto Orsi [UNESP]; Botura, Galdenoro [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2019)
A visually impaired child, if not stimulated, may face delays in motor, cognitive and social development. A simple, didactic and playful method to stimulate these skills is through toys. Although the importance of toys is recognized by child behavior' researchers, it is noted a lack of inclusive toys available in the market. This paper presents the development and evaluation of an inclusive toy prototype for visually impaired children in preschool adopting inclusive design principles in the project. We conducted an electronic research with 31 health and education professionals, evaluating their perceptions about the inclusive features of the prototype, to understand if these features can be considered as an innovation strategy to the industry and if the prototype has potential as an instrument of stimulation for visually impaired children. The results show that 90% of the participants believe that the prototype is attractive for visually impaired children and 81% that it is suitable for preschool children. In addition, 97% considered it inclusive and 64% as innovative. Regarding the stimuli provided, the agreement was always positive: 97% believe that it will stimulate touch, 65% sight, 62% motor coordination, 78% imagination, 84% curiosity, and 58% autonomy of the child.
Keywords: Inclusive design; Toy design; Visual impairment